Investigating perceptions of students' language needs at a Rwandan institution of higher learning - Magambo, Joseph (Rhodes University, Faculty of Education, Department of Education, 2009)
The site of this research is the Kigali Institute of Science and Technology (KIST). The research was undertaken to investigate first year students' perceived English language needs in order to study successfully at KIST. The research was intended to pave the way for differentiated English language syllabuses for students of varying English proficiency. It sought to answer the following questions: (1) what are students' perceived language needs in order to study through the medium of English at KIST? (2) To what extent does the current English language programme address these perceived needs? And (3) what are the differences in students' perceived language needs at different levels of proficiency? The research was carried out in an interpretive paradigm using both qualitative and quantitative methods. It took the form of a case study utilising questionnaires to collect data. Questionnaires were administered to students, mainstream subject lecturers and English lecturers. The student sample consisted of 212 students chosen from the four previously identified levels of proficiency (beginner, elementary, intermediate and advanced). The lecturer samples consisted of seven subject lecturers and eleven lecturers in English. The research tools used to collect data were administered questionnaires and document analysis. The chi-square statistical test was used to analyse quantitative data especially in establishing differences that appeared between dissimilar proficiency levels. Findings have shown that, although English is no longer a credit-bearing course, students are still interested in learning it. Students expressed a high positive perception for learning language structures, listening and speaking, and a need for reading and writing. However, although it was possible to establish stakeholders' (students, subject lecturers and lecturers in English) perceptions of students' needs, it was not easy to establish what students' real needs and difficulties in English are. Attempts to get valid answers to my questions were not conclusive. Although this research has implications for the future of English language teaching/learning at KIST there is a need for further investigation of students' needs. An important starting point would be to begin a debate at KIST about the whole issue of students' needs. Such research would exploit research tools/methods not used in this research (e.g focus group interviews and observations).
Keywords: Kigali Institute of Science, Technology and Management; English language -- Study and teaching (Higher) -- Rwanda; English language -- Study and teaching (Higher) -- Rwanda -- Foreign speakers; Universities and colleges -- Rwanda